Pengaruh Beban Kerja, Coping Stress, dan Motivasi Terhadap Produktivitas Kinerja Guru - Mayasari, Mayasari; Nainggolan, Ika Frida Varinsi; Admannur, Febby; Sitanggang, Ricky Affandy; Simanjuntak, Usrianto; Lubis, Hasrita; Safrida, Safrida (Graha Mitra Edukasi, 2024)
This research was conducted with the aim of determining the influence of workload, stress coping and motivation on teacher productivity at SMP Negeri 1 Idi, East Aceh Regency. The research was conducted using a quantitative approach, while the research respondents were 67 teachers at SMP Negeri 1 Idi, East Aceh Regency. The conclusions of the research conducted include: 1) There is a positive and significant influence between workload on teacher productivity at SMP Negeri 1 Idi, East Aceh Regency. This is proven by the coefficient value tcount < ttable, namely 3.126 > 1.668 with a significance of 0.002 < 0.05. This means that the research hypothesis H₀ is rejected and H1 is accepted. 2) There is a positive but not significant influence between stress coping on teacher productivity at SMP Negeri 1 Idi, East Aceh Regency. This is proven by the coefficient value tcount > ttable, namely 0.050 < 1.668 with a significance of 0.960 > 0.05. This means that the research hypothesis H0 is accepted and H2 is rejected. 3) There is a positive and significant influence between motivation and teacher productivity at SMP Negeri 1 Idi, East Aceh Regency. This is proven by the coefficient value tcount < ttable, namely 6.982 > 1.669 with a significance of 0.000 < 0.05. This means that the research hypothesis H₀ is rejected and H1 is accepted. 4) There is a positive influence between workload, stress coping and motivation on teacher productivity at SMP Negeri 1 Idi, East Aceh Regency. This is based on the results of research conducted using the F test (simultaneous test) that the variables consisting of workload (X1), coping stress (X2), motivation (X3) have a significant value of α 0.000 < 0.05 and the value of Fcount > Ftable ( 136,452 > 3.13). Thus, the decision is obtained that H0 is rejected and H4 is accepted. The coefficient of determination (R Square) is R Square 0.860 or equal to 86%. This figure means that the variables Workload (X1), Coping Stress (X2), Motivation (X3) simultaneously (together) influence the Teacher Productivity variable (Y) by 86%. While the remainder is 100% - 86% = 14%. This means that 14% is influenced by other variables outside the regression equation or the variables studied.